PRINSIP PRAGMATIK DALAM BAHASA JEPANG YANG TERCERMIN DALAM NOVEL ‘NORUWEI NO MORI’ KARYA HARUKI MURAKAMI - Rismorlita, Cut Erra; Prasetio, Viana Meilani; Setiorini, Dwi Wahyu (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2011)
A novel containing speech of the character. This is intended to the reader, so they can own conversations that occur between one character with another character. The speech are refers to pragmatic theory like politeness and cooperation theory, illocution and perlocution.